Social entrepreneurship in sport: a peripheral country perspective - Kamyuka, Denise; Misener, Laura; Tippett, Marisa (Frontiers in Sports and Active Living, 2023)
For the past decade, scholars have been working towards developing a robust theory of social entrepreneurship in sport (SES). However, SES theory remains void of peripheral country perspectives and thus perpetuates the Eurocentric views of entrepreneurship. This paper used a decolonial feminist lens and Whittemore and Knafl’s methodology to conduct an integrated review of SES literature written in or about a peripheral country context. The review examined how scholarship from and about this context had considered geographical and culturally specific perspectives in the development of SES theory. A total of n = 1971 papers were retrieved, with only n = 12 providing relevant peripheral country context. This scarcity of literature indicates that the current theory of SES lacks peripheral country perspectives. Many papers in this review (n = 5) are written by authors in or from a peripheral country. Their contributions to SES literature revealed the decolonial feminist approaches that centralize alternative perspectives and added plurality to the definition of SES. The findings revealed the nuanced theoretical approaches to SES and highlighted the gaps in this context. The review shows how, despite the rise in social enterprises that focus on gender equity and the economic inclusion of women, gendered studies were still very scarce.